2013
DOI: 10.4336/2013.pfb.33.76.399
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização da família Geometridae (Insecta: Lepidoptera) associada a diferentes fragmentos florestais, em Cotriguaçu, MT

Abstract: Resumo-Este trabalho teve como objetivo coletar, identificar e caracterizar faunisticamente a entomofauna de Geometridae no município de Cotriguaçu, MT, em diferentes fragmentos florestais. Foram amostrados os seguintes ambientes: plantio de Tectona grandis; plantio consorciado composto por espécies de Ficus spp., Astronium sp., Jacaranda copaia, Syzygium jambolanum e Aspidosperma sp., área de capoeira; mata ripária; e floresta nativa. O período de levantamento ocorreu no período de Julho de 2007 a Junho de 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…The species Cryptocarenus seriatus was highly increased in October, January, March, and June. Januário et al (2013) reinforced the idea that planted forests can present larger numbers of individuals than natural forests, albeit with an irregular distribution of individuals, which leads to disorderly population outbreaks and low diversity in the environment. Studying coleoborers in Hevea brasiliensis in the state of Mato Grosso, Dall'oglio and Peres Filho (1997) found population peaks of C. heveae species in the months of july and august, working with different vegetation systems in two agroforestry systems and rubber tree planting.…”
Section: Resultsmentioning
confidence: 70%
“…The species Cryptocarenus seriatus was highly increased in October, January, March, and June. Januário et al (2013) reinforced the idea that planted forests can present larger numbers of individuals than natural forests, albeit with an irregular distribution of individuals, which leads to disorderly population outbreaks and low diversity in the environment. Studying coleoborers in Hevea brasiliensis in the state of Mato Grosso, Dall'oglio and Peres Filho (1997) found population peaks of C. heveae species in the months of july and august, working with different vegetation systems in two agroforestry systems and rubber tree planting.…”
Section: Resultsmentioning
confidence: 70%
“…The Geometridae S. vulneraria is a Neotropical species widely distributed from the southern portions of United States to southern South America, including the countries in Central America (Holland, 1916;Rindge, 1973;Becker, 2002;Pitkin, 2002 (Januário et al, 2013), as well as in forest recovery fragments and natural forest in the city of Botucatu, São Paulo State (Leitão-Lima, 2002).…”
Section: Photo: Leandro Prado Ribeiromentioning
confidence: 99%
“…However, only 79 records of this family in Brazil were found in the World Lepidopteran Hostplants database (Natural History Museum London, accessed on 03/04/2020), with 35 nominal species cited. In addition, some inventories for local faunas had been carried out in Brazil, among them: Januário et al (2013), who reported 25 species collected in northern Mato Grosso state in the Amazon rainforest; Diniz, Morais and Camargo (2001), who cited 22 caterpillar species in the Cerrado biome in the Federal District; and Marconato, Dias and Penteado-Dias (2008), who recorded 22 caterpillars species associated with plants of the species Erythroxylum microphyllum A. St.-Hil. (Erythroxylaceae) in the Cerrado biome in the state of São Paulo.…”
Section: Introductionmentioning
confidence: 99%